Selves in question : interviews on Southern African auto/biography - Coullie, Judith Lütge (Writing past colonialism series., 2006)
Wide-ranging and engaging, Selves in Question considers the various ways in which auto/biographical accounts situate and question the self in contemporary southern Africa. The twenty-seven interviews presented here consider both the ontological status and the representation of the self. They remind us that the self is constantly under construction in webs of interlocution and that its status and representation are always in question. The contributors, therefore, look at ways in which auto/biographical practices contribute to placing, understanding, and troubling the self and selves in postcolonies in the current global constellation. They examine topics such as the contexts conducive to production processes; the contents and forms of auto/biographical accounts; and finally, their impact on the producers and the audience. In doing so they map out a multitude of variables--including the specific historical juncture, geo-political locations, social positions, cultures, languages, generations, and genders--in their relations to auto/biographical practices. Those interviewed include the famous and the hardly known, women and men, writers and performers who communicate in a variety of languages: Afrikaans, English, Xhosa, isiZulu, Sesotho, and Yiddish. An extensive introduction offers a general framework on the contestation of self through auto/biography, a historical overview of auto/biographical representation in South Africa up to the present time, an outline of theoretical and thematic issues at stake in southern Africa auto/biography, and extensive primary and secondary biographies. Interviewees: Breyten Breytenbach, Dennis Brutus, Valentine Cascarino, Vanitha Chetty, Wilfred Cibane, Greig Coetzee, J.M. Coetzee, Paul Faber, David Goldblatt, Stephen Gray, Dorian Haarhoff, Rayda Jacobs, Elsa Joubert, K. Limakatso Kendall, Ester Lee, Doris Lessing, Sindiwe Magona, Margaret McCord, N. Chabani Manganyi, Zolani Mkiva, Jonathan Morgan, Es'kia Mphahlele, Rob Nixon, Mpho Nthunya, Robert Scott, Gillian Slovo, Alex J. Thembela, Pieter-Dirk Uys, Johan van Wyk, Wilhelm Verwoerd, David Wolpe, D.L.P. Yali Manisi.